Optimasi Pemasaran Brand Lokal Melalui Platform E-Commerce - Mohammad Wasil; Ulya Nur Isnanini; Ari Arumningtias; Novan Firmansyah; Wulan Aprisyah; Adila Fahmi Mahendra (Jurnal Esensi Infokom : Jurnal Esensi Sistem Informasi dan Sistem Komputer, 2023)
The rapid development of technology and information in Indonesia presents a business opportunity for entrepreneurs, particularly local brands, both large and small-scale. This research aims to elucidate the marketing strategies and increase the sales volume of local brands. The research methodology employed is a descriptive approach through a literature review. One of the local brands currently gaining attention is Aerostreet, which introduces quality shoes at affordable prices through an effective branding strategy. Suboptimal offline marketing efforts prompted Aerostreet to expand its presence into the digital realm. With the adoption of online marketing through the Shopee platform, there has been a significant surge in Aerostreet's product sales volume. In addition to reaching the domestic market, Aerostreet has now successfully penetrated the international market